Problematika Perlindungan Lahan Pertanian Berkelanjutan Pasca Undang-Undang Cipta Kerja - Sumarja, FX; Rifai, Eddy; Tisnanta, Tisnanta; Saputra, Rodhi Agung (Faculty of Law, Universitas Pattimura, 2021)
Provisions of Law no. 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land (UU PLP2B) is basically intended to classify a certain area of land that is allowed for appropriate food agriculture activities. This research is to examine the problems of sustainable agricultural land protection after the Job Creation Act and find a solution. The research method is a normative research method with a statute approach and uses content analysis. The findings of this study are changes in agricultural land protection regulations that can cause significant shrinkage of agricultural land and threaten farmer groups for investment. The abolition of the obligation to provide replacement land for affected farmers is not profitable for the farmer, because he will lose his agricultural land. The solution is that the government in determining the location of development projects must avoid the use of fertile/productive agricultural land.